Reference framework for the enterprise architecture for national organizations for official statistics: Literature review - Nhabomba, A.; Alturas, B.; Alexandre, I. (Proceedings of International Conference on Information Technology and Applications. Lecture Notes in Networks and Systems, 2023)
Enterprise Architecture Frameworks (EAF) play a crucial role in organizations by providing a means to ensure that the standards for creating the information environment exist and they are properly integrated, thus enabling the creation of Enterprise Architectures (EA) that represent the structure of components, their relationships, principles and guidelines with the main purpose of supporting business. The increase in the variety and number of Information Technology Systems (ITS) in organizations, increasing their complexity and cost, while decreasing the chances of obtaining real value from these systems, makes the need for an EA even greater. This issue is very critical in organizations whose final product is information, such as the National Organizations for Official Statistics (NOOS), whose mission is to produce and disseminate official statistical information of the respective countries. Historically, NOOS have individually developed business processes and similar products using ITS that are not similar, thus making it difficult to produce consistent statistics in all areas of information. In addition, over the years, the NOOS adopted a business and technological structure and model that entails high maintenance costs that are becoming increasingly impractical and the delivery model inexcusable, and the current EAFs are not properly optimized to deal with these problems. NOOS are being increasingly challenged to respond quickly to these emerging information needs. We carried out this research through a literature review and a body of information pertinent on the topic was collected, which allowed us to demonstrate that, in order to respond to these challenges, it is necessary to have a holistic view of ITS through the definition of an EA using a reference EAF among the current ones or a new one, built from scratch.